2014
DOI: 10.3389/fonc.2014.00191
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Anti-Tumor Immunity Induced by Oncolytic Viruses

Abstract: Oncolytic viruses (OVs) not only kill cancer cells by direct lysis but also generate a significant anti-tumor immune response that allows for prolonged cancer control and in some cases cures. How to best stimulate this effect is a subject of intense investigation in the OV field. While pharmacological manipulation of the cellular innate anti-viral immune response has been shown by several groups to improve viral oncolysis and spread, it is increasingly clear that pharmacological agents can also impact the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 117 publications
(150 reference statements)
0
30
0
Order By: Relevance
“…Oncolytic viruses are novel cancer treatments that mediate antitumor activity by selectively replicating in tumors and lysing tumor cells, subsequently releasing tumor‐derived antigens to promote antitumor immunity . Oncolytic viruses can be modified to express genes that further augment the antitumor immune response . Talimogene laherparepvec is a modified herpes simplex virus (HSV) type‐1 designed to specifically replicate in and lyse tumor cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncolytic viruses are novel cancer treatments that mediate antitumor activity by selectively replicating in tumors and lysing tumor cells, subsequently releasing tumor‐derived antigens to promote antitumor immunity . Oncolytic viruses can be modified to express genes that further augment the antitumor immune response . Talimogene laherparepvec is a modified herpes simplex virus (HSV) type‐1 designed to specifically replicate in and lyse tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…GM‐CSF can act to recruit and activate antigen‐presenting cells to process and present tumor‐derived antigens to help promote tumor specific T‐cell responses . Release of immune‐stimulatory viral proteins may further enhance the antitumor immune response . Responses in uninjected tumors, including visceral metastases, have been seen in patients treated with talimogene laherparepvec (in the OPTiM study responses to talimogene laherparepvec were observed in 34% of evaluable uninjected nonvisceral and 15% of evaluable visceral lesions), indicating that an effective systemic antitumor response can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Also the intravesical instillation of CG0070 is being studied as a standalone therapy in bladder cancer patients who failed BCG-based immunotherapy [45]. Recently, combined oncolytic Ad and chemotherapy could convey stronger anti-tumor effects by providing synergistic mode of actions by oncolysis and chemotherapeutic mechanism, potentially attenuating cancer cell resistance to virotherapy or chemotherapy [37,38]. GM-CSF coding capsid chimeric Ad, CGTG-102 moves on to the phase I for advanced solid tumors, alone or in combination with cyclophosphamide chemotherapy [40,46].…”
Section: Introductionmentioning
confidence: 99%
“…In recent clinical trials, combined oncolytic Ad and chemotherapy could convey stronger anti-tumor effects by providing synergistic effects by oncolysis and chemotherapeutic mechanism, potentially attenuating cancer cell resistance to virotherapy or chemotherapy [37, 38]. Deeper understanding of complex interactions and molecular mechanisms between the oncolytic Ad, adjuvant chemotherapy or radiation therapy, and tumor must be followed the pros and cons of cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined by Forbes et al (11) from the Ottawa Hospital Research Institute, Ottawa (Canada), several approved drugs and novel small molecules can be effective tools to dampen the innate and adaptive anti-viral responses, increase the anti-tumor immune response, or both. Such approaches are discussed to be undoubtedly context dependent (e.g., tumor type and tumor site) and OV-dependent.…”
mentioning
confidence: 99%